2001
DOI: 10.1046/j.1365-2222.2001.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Having lived on a farm and protection against allergic diseases in Australia

Abstract: Having lived on a farm in Australia can confer protection against atopy in children. Further studies are needed to identify possible protective mechanisms associated with farm animals or to establish whether the protective effect is explained by other related exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 23 publications
4
113
3
1
Order By: Relevance
“…A high T-helper-1-cell immune activity may result in a lower probability of immunoglobulin E activation, the presence of which determines the development of atopic sensitization and diseases. This mechanism was suggested as a reason for possible protective effects experienced by children who grow up on farms as described by Von Ehrenstein, et al [26], Downs et al [27], and Pekkanen et al [28].…”
Section: Discussionmentioning
confidence: 88%
“…A high T-helper-1-cell immune activity may result in a lower probability of immunoglobulin E activation, the presence of which determines the development of atopic sensitization and diseases. This mechanism was suggested as a reason for possible protective effects experienced by children who grow up on farms as described by Von Ehrenstein, et al [26], Downs et al [27], and Pekkanen et al [28].…”
Section: Discussionmentioning
confidence: 88%
“…Downs and colleagues investigated asthma and atopy among children 7 to 12 years of age from two farming regions in Australia. 12 No protective effect of farming was observed among children living in a primarily crop farming region. However, the prevalence of asthma and atopy was reduced among farm children living in a region with both livestock and crop farming compared to their non-farm peers from the same region.…”
Section: Asthma and Atopy In Farming Populationsmentioning
confidence: 98%
“…Several recent studies from Europe, Canada, and Australia have suggested that agricultural exposures may protect children from developing asthma and atopy. [5][6][7][8][9][10][11][12][13][14][15][16][17] However, these findings are not all consistent, and research has not yet identified the underlying mechanisms of this association. Further, this suggested protection in children contrasts with a host of studies from the occupational literature that suggest adult farmers are at increased risk of respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
“…The observed protective effects of farming on allergies and asthma have been particularly strong for animal contact [5,10,11,13,15,20]. Farm animals are associated with high exposures to microorganisms, in particular bacterial endotoxin [45].…”
Section: Protective Exposuresmentioning
confidence: 99%
“…A related issue is that a number of studies have found consistently low prevalences of allergies and asthma in farmers' children, both in high-income countries such as Canada, the USA, Australia, New Zealand and Europe [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and in lowincome countries including Mongolia and Southern Africa [21,22]. These protective effects for allergies and asthma have also been observed in adult farmers [23][24][25][26][27][28][29][30][31][32][33][34][35][36], despite the increased risks of other respiratory conditions, such as chronic obstructive pulmonary disease, reduced lung function and farmers' lung [37].…”
mentioning
confidence: 99%